Wanted List-Based Drug Law Enforcement: Effective Strategy or Mere Formality? - Thie, Naysa Andrea; Adhari, Ade (Jurnal Ilmu Hukum Kyadiren, 2025)
The widespread abuse of narcotics in Indonesia represents a multifaceted issue, significantly exacerbated by weaknesses within the law enforcement system—particularly in the arrest of individuals listed on the Wanted Persons List (DPO). This study aims to (1) identify the legal procedures for determining DPO status, (2) evaluate the strategies and operational challenges involved in the arrest process, and (3) analyze the role of information technology and inter-agency cooperation in enhancing the effectiveness of law enforcement. Employing an empirical juridical method with a qualitative approach, the research draws upon document analysis and in-depth interviews with law enforcement personnel. The findings reveal that, although the legal foundation for determining DPO status is well established, its implementation is hindered by structural barriers, limited inter-agency coordination, and the suboptimal application of digital technologies. The study concludes by underscoring the urgent need for the integration of digital systems, the reinforcement of cross-institutional collaboration, and the enhancement of human resource capacity to effectively support the eradication of narcotics-related crimes in Indonesia.